Aminoglycoside Antibiotics: New Insights into the Biosynthetic Machinery of Old Drugs. Issue 1 (12th October 2015) - Kudo, Fumitaka; Eguchi, Tadashi
Abstract: 2‐Deoxystreptamine (2DOS) is the unique chemically stable aminocyclitol scaffold of clinically important aminoglycoside antibiotics such as neomycin, kanamycin, and gentamicin, which are produced by Actinomycetes . The 2DOS core can be decorated with various deoxyaminosugars to make structurally diverse pseudo‐oligosaccharides. After the discovery of biosynthetic gene clusters for 2DOS‐containing aminoglycoside antibiotics, the function of each biosynthetic enzyme has been extensively elucidated. The common biosynthetic intermediates 2DOS, paromamine and ribostamycin are constructed by conserved enzymes encoded in the gene clusters. The biosynthetic intermediates are then converted to characteristic architectures by unique enzymes encoded in each biosynthetic gene cluster. In this Personal Account, we summarize both common biosynthetic pathways and the pathways used for structural diversification. Abstract : Step‐by‐step enzymatic reactions to construct the common biosynthetic intermediates in the biosynthesis of clinically important 2‐deoxystreptamine‐containing aminoglycoside antibiotics such as neomycin and kanamycin are summarized. Furthermore, recently characterized unique enzymes that are responsible for the diversification of this class of antibiotics are described.